Antiteratogenic Effects of Leaf Extract of Mentha Cordifolia Opiz. (Mint), Allium Sativum L. (Garlic), and Pterocarpus Indicus Willid. (Narra) on Mus Musculus (White Mice) - Sumagaysay, James B. (JPAIR Multidisciplinary Research, 2008)
This study compared the antiteratogenic effects of leaf extracts from mint (Mentha cordifolia Opiz.), garlic (Allium sativum L.), and narra (Pterocarpus indicus Willd.) in mice. The research aimed to assess fertility, implantation, and gestation indices, as well as the percentage of dead implants and female resorptions. It also examined the gross anatomy of fetuses and compared sperm morphology across treatments. Twenty-five male and fifty female mice were randomly assigned to five groups: distilled water (T0+), tetracycline (T0-), tetracycline with mint extract (T1), tetracycline with garlic extract (T2), and tetracycline with narra extract (T3). Treatments were administered subcutaneously for six days, and sperm morphology was assessed post-mating. Results showed that narra, mint, and garlic extracts significantly enhanced fertility and implantation rates while reducing resorptions and dead implants. No congenital malformations were observed in pups, and sperm morphology improved in treated groups. The study highlights the potential antiteratogenic benefits of these plant extracts.